La Enfermería frente a la Inteligencia Artificial: cuidar sin perder lo humano. - Soprano, Sabrina (Visión de Enfermería Actualizada, 2026)
The article focuses on the impact of artificial intelligence (AI) and digital transformation in Nursing, highlighting how these technologies are changing the organization and management of healthcare. It points out that, although AI offers benefits such as process optimization and improved clinical decision-making, it also poses ethical challenges and risks of dehumanization in care. The need for nursing professionals to develop competencies in digital literacy, bioethics, and technological security is emphasized, as well as their active participation in healthcare transformation. Furthermore, it is stressed that technology should complement, not replace, clinical judgment and the human dimension of care, maintaining empathy and therapeutic communication as irreplaceable elements.